(untitled) (Quest Journal of Management and Social Sciences, 2023)
Purpose: This study examines the relationship between leadership style and organizational justice among bankers in commercial banks in Kathmandu Valley. It also investigates the effect of gender on the study variables. Design/Methodology/Approach: It uses a quantitative approach comprising a self-administrated questionnaire to test hypotheses from 151 bankers. Correlation and one-way analysis of variance (ANOVA) are used for data analysis. Findings: The results suggest that a positive relationship between leadership style and organizational justice exists. Moreover, it is found that there exists a significant difference between male and female bankers in transformational leadership but not in transactional leadership. Further, gender has significant differences among bankers in relation to organizational justice and its sub-dimensions. Implications: This research could help understand the importance of leadership in banks to prevail in organizational justice. It reflects the importance of creating a diverse workforce, especially the necessity of female employees to promote fairness in the organization. Keywords: Leadership style, Gender, Transactional leadership, Transformational leadership, Organizational Justice Paper Type: Research Paper